2017
DOI: 10.2147/ijn.s129266
|View full text |Cite
|
Sign up to set email alerts
|

Killing malignant melanoma cells with protoporphyrin IX-loaded polymersome-mediated photodynamic therapy and cold atmospheric plasma

Abstract: Traditional cancer treatments contain several limitations such as incomplete ablation and multidrug resistance. It is known that photodynamic therapy (PDT) is an effective treatment for several tumor types especially melanoma cells. During the PDT process, protoporphyrin IX (PpIX), an effective photosensitizer, can selectively kill cancer cells by activating a special light source. When tumor cells encapsulate a photosensitizer, they can be easily excited into an excited state by a light source. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 22 publications
0
24
0
1
Order By: Relevance
“…Finally, it is curious and interesting to note that cold atmospheric plasma has been employed together with nanotherapeutics (protoporphyrin IX-loaded polymersomes) as an alternative light source in order to kill melanoma cells by photodynamic therapy [188].…”
Section: Cold Atmospheric Plasmamentioning
confidence: 99%
“…Finally, it is curious and interesting to note that cold atmospheric plasma has been employed together with nanotherapeutics (protoporphyrin IX-loaded polymersomes) as an alternative light source in order to kill melanoma cells by photodynamic therapy [188].…”
Section: Cold Atmospheric Plasmamentioning
confidence: 99%
“…This includes brain cancer, skin cancer, breast cancer, colorectal cancer, lung cancer, cervical cancer, leukemia, hepatoma, head and neck cancer, as well as osteosarcoma [5][6][7][8]. Moreover, CAP treatment can be combined with chemotherapy [9][10][11][12], nanoparticles [13][14][15][16][17], hyperthermia [18], radiotherapy [18,19], photodynamic therapy [20,21], and magnetic field [22]. Several clinical studies reported the use of CAP for treatment of (pre-) cancerous tissues [23] and two clinical trials using CAP are currently undergoing treatment of cervical intraepithelial neoplasia (ClinicalTrials.gov Identifier: NCT03218436) and Canady Helios cold plasma scalpel treatment at the surgical margin and macroscopic tumor sites (ClinicalTrials.gov Identifier: NCT04267575).…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that cancer cells can be effectively killed by using a CAP light source with a wide range of wavelengths, compared with UV light sources. After CAP irradiation, melanoma cell killing efficiency significantly increased to 80% when compared with no light source (45%) or a UV light source (65%) (Wang, Geilich, Keidar, & Webster, 2017). …”
Section: Anticancer Therapeutics and Nanoparticle-based Delivery Agentsmentioning
confidence: 99%